Effects of accelerated carbonation on fine incineration bottom ash: CO2 uptake, strength improvement, densification, and heavy metal immobilization - Sun, Xinlei (2024)
Incinerating municipal solid waste (MSW) can effectively reduce its mass and volume while producing electricity. However, this process generates incineration bottom ash (IBA), which is an aggregate-like waste containing heavy metals. Due to the higher heavy metal contents, fine IBA can be removed from total IBA and treated separately to promote the use of IBA. Furthermore, MSW incineration generates carbon dioxide (CO2), which is another concern. In this context, it is beneficial to use accelerated carbonation to treat fine IBA, because it can not only contribute to carbon capture but also provide carbonated IBA that may be utilized as aggregates in civil engineering. The accelerated carbonation process of fine IBA is affected by many parameters. Therefore, this study investigated the effects of CO2 pressure (PCO2), initial water content (wi), and carbonation time on the properties of carbonated IBA, including CO2 uptake, unconfined compressive strength (UCS), density, and leaching of heavy metals. The evolution of mineralogy and microstructure of carbonated IBA was also analyzed. The results showed that IBA with wi of 15% and PCO2 of 200 kPa could achieve a CO2 uptake of 6% of IBA mass. The carbonation time significantly affected UCS and dry density of carbonated IBA. As the carbonation time increased from 0 h to 120 h, the UCS increased from 67 kPa to 691 kPa while the dry density increased from 1.38 g/cm3 to 1.51 g/cm3. Compared with untreated IBA, the leaching concentrations of Cu, Cr, Zn, and Pb from carbonated IBA were reduced significantly. As the carbonation time increased, the microstructure of carbonated IBA became denser. This densified structure was one of the reasons for the strength improvement and dry density increment of carbonated IBA.